2010
DOI: 10.1098/rspb.2010.1254
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of microbial phototrophs in the dry valleys of the high Himalayas and Antarctica

Abstract: High-elevation valleys in dry areas of the Himalayas are among the most extreme, yet least explored environments on Earth. These barren, rocky valleys are subjected to year-round temperature fluctuations across the freezing point and very low availability of water and nutrients, causing previous workers to hypothesize that no photoautotrophic life (primary producers) exists in these locations. However, there has been no work using modern biogeochemical or culture-independent molecular methods to test the hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
62
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 40 publications
5
62
1
Order By: Relevance
“…These included 18S data sets from unvegetated sites in the high Himalayas (Schmidt et al 2011), the high Andes of Peru (Nemergut et al 2007), Denali National Park, Alaska (Darcy and Schmidt 2016), Mt Kilimanjaro (Vimercati et al unpubl. ), and along the continental divide in Colorado.…”
Section: Landscape Patterns Of Naganishia Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…These included 18S data sets from unvegetated sites in the high Himalayas (Schmidt et al 2011), the high Andes of Peru (Nemergut et al 2007), Denali National Park, Alaska (Darcy and Schmidt 2016), Mt Kilimanjaro (Vimercati et al unpubl. ), and along the continental divide in Colorado.…”
Section: Landscape Patterns Of Naganishia Distributionmentioning
confidence: 99%
“…Importantly, these sites were also the only sampled sites (among the global sites listed above) that had soil pH values (pH 4.5) similar to those found on the three volcanoes (Table 1). All the other sites (Alaska, Peru and Nepal) had soil pH values above 7.5 (Nemergut et al 2007; Schmidt et al 2011; Darcy and Schmidt 2016). On-going work at the Niwot Ridge LTER site in Colorado and at sites on Volcán Llullaillaco are attempting to parse out the effects of elevation versus pH on the landscape distribution patterns of N. friedmannii (Gendron et al, unpublished data).…”
Section: Landscape Patterns Of Naganishia Distributionmentioning
confidence: 99%
“…Embryophytes have dominated the terrestrial environment since the late Ordovician, and some have become secondarily adapted to aquatic environments, including holoaquatic marine species that form extensive beds of seagrass. Several green algae have adapted to highly specialised or extreme environments, such as hot or cold deserts De Wever et al, 2009;Schmidt et al, 2011), hypersaline habitats (Vinogradova & Darienko, 2008), acidic waters with extreme concentrations of heavy metals (Zettler et al, 2002), marine deep waters (Zechman et al, 2010) and deep-sea hydrothermal vents (Edgcomb et al, 2002). Some green algal groups, i.e., Trentepohliales, are exclusively terrestrial and never found in aquatic environments .…”
mentioning
confidence: 99%
“…1). The presence of these uncultured psychrophilic and/or psychrotolerant cyanobacteria in the extreme environments has recently been identified only by culture-independent approaches such as 16S rRNA gene clone library screening or automated ribosomal ITS analysis fingerprinting (Wood et al 2008;Xiang et al 2009;Jungblut et al 2010;Schmidt et al 2011;Zeglin et al 2011;Kleinteich et al 2012). Therefore, strain KNUA009 represents the first laboratory culture to be assigned to a group of uncultured cyanobacteria residing in the cryosphere.…”
Section: Discussionmentioning
confidence: 99%